Respuesta :

Answer:

[tex]\boxed{\mathrm{B}}[/tex]

Step-by-step explanation:

[tex]f(x)=\frac{x+1}{x}[/tex]

[tex]y=\frac{x+1}{x}[/tex]

Make x as subject.

Multiply both sides by x.

[tex]yx=x+1[/tex]

Subtract both sides by x.

[tex]yx-x=1[/tex]

Factor out x.

[tex]x(y-1)=1[/tex]

Divide both sides by y-1.

[tex]x=\frac{1}{y-1}[/tex]

Switch variables.

[tex]y=\frac{1}{x-1}[/tex]

Answer:

[tex] {f}^{ - 1} (x) = \frac{1}{x - 1} [/tex]

Option B is the correct option.

Step-by-step explanation:

Let y = f ( x )

[tex]y = \frac{x + 1}{x} [/tex]

Apply cross product property

[tex]xy = x + 1[/tex]

Move 'x' to L.H.S and change it's sign

[tex]xy - x = 1[/tex]

Take x as common

[tex]x(y - 1) = 1[/tex]

[tex]x = \frac{1}{y - 1} [/tex]

Replace x by f ⁻¹(x) and y by x

[tex] {f}^{ - 1} (x) = \frac{1}{x - 1} [/tex]

Hence, Option B is the correct option.

Hope this helps..

Best regards!!

ACCESS MORE